High‐resolution manometry in patients with eosinophilic esophagitis under topical steroid therapy—a prospective observational study (HIMEOS‐study). Issue 4 (17th February 2016) - Nennstiel, S.; Bajbouj, M.; Becker, V.; Slotta‐Huspenina, J.; Wagenpfeil, S.; Schmid, R. M.; Schlag, C.
Abstract: Background: In eosinophilic esophagitis (EoE), dysphagia, which might reflect esophageal dysmotility, is the most common symptom. High‐resolution manometry (HRM) has become widely accepted for evaluating esophageal motility disorders, but to date has been sparsely examined in EoE patients, particularly under therapy. The aim of this study was to evaluate HRM in symptomatic EoE‐patients under topical steroid treatment. Methods: In this prospective observational study, symptomatic EoE patients received HRM‐examinations before and after 8 weeks of topical steroid treatment with budesonide. All HRM‐abnormalities were assessed and interpreted according to the Chicago classification. The primary endpoint was the influence of topical steroid treatment on the intrabolus pressure (IBP). Clinical symptoms, endoscopic findings and histological esophageal eosinophilic load were also reported. Key Results: Twenty symptomatic EoE patients were included. Overall success of budesonide therapy was 85% regarding complete histologic remission and 80% regarding complete clinical remission. High‐resolution manometry showed abnormal esophageal motility in 35% of patients at baseline, which was resolved after therapy in 86% of these patients. Most frequent HRM‐findings were early pan‐esophageal pressurizations and weak persitalsis. There was no significant reduction of the IBP under therapy (before: 12.5 ± 4.9 mmHg, after: 10.9 ± 2.9 mmHg; p = 0.119). Conclusions & Inferences: Although dysphagia is the leading symptom of EoE, HRM is able to identify esophageal motility disorders in only some EoE patients. Observed motility disorders resolve after successful treatment in almost all of these patients. Intrabolus pressure does not seem an optimal parameter for the monitoring of successful treatment response in EoE patients. Abstract : In order to identify potential HRM‐abnormalities in EoE‐patients and to evaluate the effect of topical steroid treatment on these abnormalities, 20 EoE‐patients were examined by HRM before and after 8 weeks of steroid therapy. High‐resolution manometry showed abnormal findings in 35% of EoE‐patients at baseline, most frequently early pan‐esophageal pressurizations, which resolved after therapy in 86% of these patients.